Endogenous Methyl Salicylate in Pathogen-Inoculated Tobacco Plants - Seskar, Mirjana (American Society of Plant Physiologists, 1998)
The tobacco (Nicotiana tabacum) cultivar Xanthi-nc (genotype NN) produces high levels of salicylic acid (SA) after inoculation with the tobacco mosaic virus (TMV). Gaseous methyl salicylate (MeSA), a major volatile produced in TMV-inoculated tobacco plants, was recently shown to be an airborne defense signal. Using an assay developed to measure the MeSA present in tissue, we have shown that in TMV-inoculated tobacco plants the level of MeSA increases dramatically, paralleling increases in SA. MeSA accumulation was also observed in upper, noninoculated leaves. In TMV-inoculated tobacco shifted from 32 to 24°C, the MeSA concentration increased from nondetectable levels to 2318 ng/g fresh weight 12 h after the temperature shift, but subsequently decreased with the onset of the hypersensitive response. Similar results were observed in plants inoculated with Pseudomonas syringae pathovar phaseolicola, in which MeSA levels were highest just before the hypersensitive response-induced tissue desiccation. Transgenic NahG plants unable to accumulate SA also did not accumulate MeSA after TMV inoculation, and did not show increased resistance to TMV following MeSA treatment. Based on the spatial and temporal kinetics of its accumulation, we conclude that tissue MeSA may play a role similar to that of volatile MeSA in the pathogen-induced defense response.